Mendelian randomization study shows no causal relationship between circulating urate levels and Parkinson's disease. Issue 2 (14th September 2018) - Kia, Demis A.; Noyce, Alastair J.; White, Jon; Speed, Doug; Nicolas, Aude; ,; Burgess, Stephen; Lawlor, Debbie A.; Davey Smith, George; Singleton, Andrew; Nalls, Mike A.; Sofat, Reecha; et al.
Abstract : Objective: Observational studies have shown that increased plasma urate is associated with lower risk of Parkinson's disease (PD), but these studies were not designed to test causality. If a causal relationship exists, then modulating plasma urate levels could be a potential preventive avenue for PD. We used a large two‐sample Mendelian randomization (MR) design to assess for a causal relationship between plasma urate and PD risk. Methods: We used a genetic instrument consisting of 31 independent loci for plasma urate on a case‐control genome‐wide association study data set, which included 13, 708 PD cases and 95, 282 controls. Individual effect estimates for each SNP were combined using the inverse‐variance weighted (IVW) method. Two additional methods, MR‐Egger and a penalized weighted median (PWM)‐based approach, were used to assess potential bias attributed to pleiotropy or invalid instruments. Results: We found no evidence for a causal relationship between urate and PD, with an effect estimate from the IVW method of odds ratio (OR) 1.03 (95% confidence interval [CI], 0.88–1.20) per 1‐standard‐deviation increase in plasma urate levels. MR Egger and PWM analyses yielded similar estimates (OR, 0.99 [95% CI, 0.83–1.17] and 0.99 [95% CI, 0.86−1.14], respectively). Interpretation: We did not find evidence for a linear causal protective effect by urate on PD risk. The associations observed in previous observational studies may be, in part, attributed to confounding or reverse causality. In the context of the present findings, strategies to elevate circulating urate levels may not reduce overall PD risk. Ann Neurol 2018;84:191–199